Functional capacity and risk of frailty syndrome in 85-year-old and older women living in nursing homes in Poland - Kaczorowska, Antonina; Sebastjan, Anna; Kołodziej, Małgorzata; Kozieł, Sławomir; Tomczak, Mariusz; Ignasiak, Zofia (Anthropological Review, 2021)
Maintaining sufficient physical fitness to prevent any limitations in performing activities of daily living and to be functionally independent is of great importance for both longevity and quality of life in older adults. Aim of the study was to evaluate functional physical fitness of women aged 85 years and older, residents of nursing homes, in the Polish population and to assess the risk of frailty syndrome. The study involved 17 women aged 85 years or older, residents of nursing homes in the Lower Silesian voivodeship. The Senior Fitness Test was used to assess functional fitness. The results of functional fitness tests were related to the standards for the elderly population in Poland and to the reference standards for maintaining independence. In addition, hand grip strength level was measured using a hand dynamometer, height and weight were measured, and BMI was calculated. 15-item version of the Geriatric Depression Scale was used to assess the level of depression. We used 3 of the 5 proposed criteria from the Cardiovascular Health Study Frailty Index to assess the presence of frailty syndrome: gait speed, level of hand grip strength, and the presence of depression. The results of the Senior Fitness Test demonstrate the low level of functional fitness of female nursing home residents. A large percentage of the women surveyed are below the standard values developed for Polish seniors. The weakest results were in the timed up and go test, with more than 94% of the women tested falling outside the standard ranges. The mean results of all samples do not meet the developed reference standards for maintaining independence. No non-frail person was found among the study participants and the vast majority were at risk for frailty syndrome. Most of the studied women do not meet functional fitness standards developed for the Polish population, as well as reference standards for maintaining independence. Nursing home residents over the age of 85 are at risk for frailty syndrome.